Evidence Based Case Report: Secukinumab versus golimumab for Ankylosing Spondylitis Patients - Yosafat Sebastian Prayogo (Indonesian Rheumatology Associantion, 2025)
Background: Ankylosing spondylitis is a chronic inflammation of the axial spine and joints that can lead to a wide spectrum of clinical manifestations, with chronic back pain and progressive vertebrae stiffness being two hallmark symptoms. The choice of medication for ankylosing spondylitis depends on both efficacy and cost. This study aims to compare Secukinumab, the cheapest and only available anti-interleukin-17, against Golimumab, a TNF-alpha inhibitor, in terms of efficacy and cost. Methods: A systematic search was conducted until October 30th, 2023, using keywords such as ankylosing spondylitis, secukinumab, golimumab, ASAS20, and their synonyms on databases including PubMed, Embase, SCOPUS, and Cochrane to find relevant studies. Critical appraisal of included studies was performed using the Oxford Center of Evidence-based Medicine (CEBM) tools for harm scenarios. Results: Three eligible articles were collected, observing both Secukinumab and Golimumab with different doses and administration routes. Chen et al.'s comparative analysis between secukinumab 150 mg and golimumab 50 mg revealed an odds ratio (OR) (95% confidence interval (CI)) of 1.19 (0.03-8.94), while secukinumab 150 mg against golimumab 100 mg presented an OR of 1.45 (0.03- 11.98). Zhang et al.'s comparison results between golimumab and secukinumab yielded an OR of 0.62 (0.20-1.89). Finally, Deodhar et al. analyzed different doses of secukinumab and golimumab with an OR range of 1.04-1.15 (0.4-3.11). Conclusion: Both secukinumab and golimumab showed comparable results in ASAS20, exhibiting insignificant differences in the superiority of ASAS20 improvement. However, the cost-effectiveness and personal drug choice need to be evaluated to add further considerations to the medication choice.